Training Children's Interests and Talents Through Talent-Based Activities at TK Aisyiyah Busthanul Athfal Bebekan Taman-Sepanjang - Hafida Kurnia Rahmasari; Sabrina Rizky Amalia; Luluk Iffatur Rocmah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
The early years of childhood are a critical period for identifying and nurturing talents and interests to support holistic development. This study aimed to explore the role of teachers in developing students' talents and interests through talent-based activities at TK Aisyiyah Bustanul Athfal Bebekan Sepanjang. A qualitative research design was employed, utilizing observations, interviews, and documentation to gather data from teachers, students, and parents. The research examined strategies, methods, and challenges in facilitating talent and interest development, with a focus on teacher involvement, school environment support, and parental roles. Results revealed that while talent-based activities enhance student engagement and potential exploration, their implementation is hindered by limited resources, insufficient variety in activities, and time constraints. Despite these challenges, teachers play a significant role in fostering enthusiasm and identifying latent abilities. This research highlights the novelty of integrating structured talent-based activities into early childhood education, emphasizing their potential in creating a supportive learning environment that aligns with individual interests. The findings contribute to developing more effective educational practices to optimize the golden phase of children's development.